TOURISM DEVELOPMENT IN THE BELARUSIAN PART OF THE AUGUSTOW CANAL - Sialverstava, Sviatlana; Bogusz, Tatiana; Roman, Michał (Turystyka i Rozwój Regionalny, 2018)
The Augustow Canal basin currently displays the most potential for the development of tourism within the Republic of Belarus. Its convenient location on the border with Lithuania and Poland creates the possibility to develop both international as well ascross-bordertourism. The Belarusian portion of the Augustow Canal is home to over fifty interesting historical and cultural attractions which, along with the canal itself, create a lot of potential for exploratory tourism. This area is a part of the Grodno Forest biosphere nature preserve and as such makes its natural resources available to tourists interested in active and health tourism. Within the area of the reservation the development of tourism related infrastructure is possible only as it relates to agritourism businesses, which makes the creation of a model for their functioning essential. Remembering the specific character of the area this is an important requirement since the Canal basin is within the border zone which holds a special status in Belarus. Access to this area requires a special permit and unrestricted movement within the border zone is prohibited. In 2016 the Augustow Canal basin as well as the city of Grodno which is located 30 kilometers from this body of water has been declared a visa-free zone. Defining rules for the governing of the functioning of agritourism farms within the border zone, the protected area and visa-free region is essential. The creation of a cluster within which detailed guidelines and preferences for both the owners as well as the guests of such businesses located in the Belorussian portion of the Canal seems to be one of the solutions for this problem.